Sacred Science and the Ecological Epistemological Crisis: Revitalizing Sufi Wisdom in Restoring Seyyed Hossein Nasr's Sacred Worldview - Iyad Suryadi; Saeful Anwar (UIN Sunan Gunung Djati Bandung, 2026)
This study analyzes the concept of Scientia Sacra in Seyyed Hossein Nasr's thought as an epistemological framework for addressing the modern ecological crisis by revitalizing Sufi wisdom. It is based on the assumption that the global environmental crisis is fundamentally an epistemological and spiritual crisis caused by the desacralization of knowledge and nature within secular modernity. The study employs the concepts of Scientia Sacra, Islamic ecotheology, the desacralization of knowledge, and Sufi wisdom, including dhikr, muraqabah, khalwah, wahdat al-wujud, and zuhd, as foundations for ecological consciousness. Using a qualitative philosophical-critical library research approach, the analysis examines Nasr’s major works, particularly Knowledge and the Sacred, Man and Nature, and Religion and the Order of Nature, supported by international literature on ecotheology, environmental philosophy, and ecological Sufism. The findings show that Scientia Sacra provides an epistemological paradigm integrating scientific, spiritual, and ethical dimensions in understanding the relationship between humanity and nature. Sufi wisdom functions as a practical mechanism for transforming ecological consciousness and environmental ethics, while the ecological crisis is traced to a reductionist scientific paradigm separating knowledge from transcendental values. Nevertheless, integrating sacred epistemology with modern scientific methodology remains challenging due to issues of scientific objectivity, cultural plurality, and empirical operationalization. The study recommends spiritually grounded ecological education, stronger dialogue between scientific and religious communities, environmentally oriented public policies incorporating sacred values, and the revitalization of Sufi practices to foster sustainable ecological consciousness and advance Islamic ecotheology and environmental philosophy.